Energy Poverty in Rural Bangladesh - Barnes, Douglas F.; Khandker, Shahidur R.; Samad, Hussain A. (2012)
Energy poverty is a well-established concept among energy and development specialists. International development organizations frequently cite energy-poverty alleviation as a necessary condition to reduce income poverty. Several approaches used to measure energy poverty over the past 20 years have defined the energy poverty line as the minimum quantity of physical energy needed to perform such basic tasks as cooking and lighting. This paper uses a demand-based approach to define the energy poverty line as the threshold point at which energy consumption begins to rise with increases in household income. At or below this threshold point, households consume a bare minimum level of energy and should be considered energy poor. This approach was applied using cross-sectional data from a comprehensive 2004 household survey representative of rural Bangladesh. The findings suggest that some 58 percent of rural households in Bangladesh are energy poor, versus 45 percent that are income poor. The findings also suggest that policies to support rural electrification and greater use of improved biomass stoves might play a significant role in reducing energy poverty.